KONSEP PENDIDIKAN ISLAM DAN TOLERANSI DALAM FILM SANG PENCERAH - Muhammad Girindrawardana Agus Putra; Muhammad Nur Salim (Menara Tebuireng, 2020)
The context of the title of this research is how important it is to pay attention and examine content in films that are worth watching, especially films with religious genre. In the film the enlightener, there is a discussion of the concepts of education and tolerance. From the understanding and content of the film, viewers and educators can emulate the struggles of previous scholars and heroes. Moreover, the film hints at accepting many useful new things and an open attitude towards the problems of the times so that Muslims can respond to the times. The focus of this research is divided into three: (1) What is the concept of Islamic education in the film â€œSang Pencerahâ€?. (2) How about tolerance in the film "Sang Pencerah"?. (3) What is the contribution of the film "Sang Pencerah" in the world of Islamic education?. The type of approach in this research is the type of research used is library research (library research). The data collection technique in this research is documentation technique, both obtained from primary and secondary sources. The data analysis technique in this research is content analysis or content analysis. The results of the data indicate that: (1) in the film "Sang Pencerah" the concept of education contained in it is a process of transinternalizing Islamic knowledge from an educator to students through teaching, habituation, guidance, nurturing, supervision and development of its potential. In order to achieve harmony and perfection in this world and the hereafter. (2) The attitude of tolerance in the film "Sang Pencerah is in the form of respecting and allowing a stand, opinion, view, belief or others that are different from one's own position." (3) The contribution of the film "Sang Pencerah" in the world of education is to open new perspectives in developing filthiness according to the times.